Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan Di PT. BUMI DAYA PLAZA - Syuhada Bachri Osama A.B; Muhamad Azis Firdaus; Widhi Ariyo Bimo (CV. ITTC INDONESIA, 2025)
The purpose of this study was to see the effect of training and motivation on employee performance of PT Bumi Daya Plaza, both partially and simultaneously. This study uses a quantitative approach and data collection techniques using questionnaires, with a sample of 50 respondents. The results of the multiple regression analysis test are Y = 6.031 + 0.484 X1 + 0.378 X2, the correlation test results have an interval location between (0.800 - 1.000), and the determination test has a variable contribution X1 to Y of 63.5%, X2 to Y 60.3%, and together X1 and X2 to Y of 68.6%, which means that the independent variable has a strong and positive relationship to the dependent variable. The results of the training t test obtained the results of t count> t table (9.140> 1.675) means Ha1 is accepted and Ho1 is rejected, the work motivation t test obtained the results (8.543> 1.675) means Ha2 is accepted and Ho2 is rejected, and the f test results are (51.401> 3.18) means Ha1 is accepted and Ho3 is rejected. From these data it can be concluded that training and motivation affect the performance of employees of PT Bumi Daya Plaza.